Growth performance of seaweed (Kappapicus alvarezii) in tissue culture with immersion of NPK and TSP fertilizer - Sinung Rahardjo; Ratna Suharti; Deby Tiara Sandi; Hany Handajani (Universitas Muhammadiyah Malang, 2022)
Kappapicus alvarezii is an important economic commodity of seaweed to be developed in Indonesia. In the context of its development, seeds from tissue culture are needed.The aim of this research is to examine the growth of seaweed by immersing NPK, TSP and combination fertilizers between NPK + TSP on absolute weight, Specific Growth Rate (SGR) and morphological growth including talus length and seaweed talus diameter. This research was conducted from March 2 to May 15, 2020 in the waters of Sumberkencono Village, Wongsorejo Sub-District, Banyuwangi District, East Java. This study uses Kappaphycus alvarezii seaweed seedlings from tissue culture results from the Situbondo Brackish Aquaculture Fisheries Center, and uses treatment fertilizers, namely NPK fertilizer with 15% Nitrogen (N) composition, Phosphate (P2O5) 15%, and Potassium (K) 15% at a dose of 2 g / l and TSP fertilizer with an element composition of Phosphate (P2O5) 18% at a dose of 2 g / l, as well as a combination of NPK fertilizer 1 g / l and TSP 1g / l soaked for 15 minutes and control or without soaking. From the results of the research, obtained weight growth of seaweed by immersing NPK + TSP obtained good growth (Absolute Weight 57.48 grams, SGR 7.21%, talus length 8.5 cm, diameter 6.52 mm), then NPK treatment (Weight Absolute 37.80 grams, SGR 6.13%, Talus length 8.1 cm, diameter 6.43 mm), TSP treatment (Absolute Weight 31.6 grams, SGR 5.69%, Talus length 7.9 cm, diameter 6.36 mm) followed by control (Absolute Weight 24.8 grams, SGR 5.10%, Talus length 7.6 cm, diameter 6.32 mm).